2010
DOI: 10.3168/jds.2009-2977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary concentrate on rumen fermentation, digestibility, and nitrogen losses in dairy cows

Abstract: The objective of this experiment was to investigate the effect of level of dietary concentrate on rumen fermentation, digestibility, and N losses in lactating dairy cows. The experiment was a replicated 3x3 Latin square design with 6 cows and 16-d adaptation periods. Ruminal contents were exchanged between cows at the beginning of each adaptation period. Data for 2 of the diets tested in this experiment are presented here. The diets contained (dry matter basis): 52% (LowC; control) and 72% (HighC) concentrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
103
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 52 publications
28
103
4
2
Order By: Relevance
“…= 2.30). The positive effect of CP on OMd, despite an increase in DMI as seen before, was likely the outcome of an increase in the activity of rumen microorganisms allowed by a greater N availability (Agle et al, 2010). The combined effects of dietary CP on DMI and OMd result in a large increase in DOMI, and therefore in ME intake as a response to dietary CP, which was also partly the outcome of the simultaneous increase of NDF as CP decreased.…”
Section: Omdmentioning
confidence: 52%
“…= 2.30). The positive effect of CP on OMd, despite an increase in DMI as seen before, was likely the outcome of an increase in the activity of rumen microorganisms allowed by a greater N availability (Agle et al, 2010). The combined effects of dietary CP on DMI and OMd result in a large increase in DOMI, and therefore in ME intake as a response to dietary CP, which was also partly the outcome of the simultaneous increase of NDF as CP decreased.…”
Section: Omdmentioning
confidence: 52%
“…Moreover, rapidly-fermenting diets reduce methane production by decreasing ruminal pH, which affects the growth of methanogens, protozoa (Hook et al, 2011) and cellulolytic bacteria (Sung et al, 2007), and increases passage rate, which reduces protozoans and, thereby, interspecies hydrogen transfer (Kumar et al, 2013). Agle et al (2010) reported that diets with higher proportion of non-structural carbohydrates (52 and 72%) resulted in numerically lower methane emissions (1.5 vs. 3.4 g/hour, respectively), although results showed no difference due to high variability. A recent study in grazing Holstein Friesian cows found that concentrate level (2, 4, 6, and 8 Kg/cow/day) had no impact on methane emissions (287,273,272, and 277 g/day, respectively).…”
Section: Starch and Methanogenesismentioning
confidence: 99%
“…The elevated propionate concentration induced by propylene glycol administration could also explain the elevated protein yield on day 8 post-estrus for the treatment group relative to the controls (Agle et al, 2010). One might assume that these changes in milk composition were due to changes in dry matter intake.…”
Section: Discussionmentioning
confidence: 99%